Agglomeration Economies and Location Choices by Foreign Firms in Vietnam - Dinh Thi Thanh Binh (FIW - Research Centre International Economics, 2010)
This paper studies the effects of agglomeration economies on the location choices by foreign firms in Vietnam. By using a large dataset that provides detailed information about individual firms, the study examines the location choices by 568 newly created foreign firms in 2005 in about 150 different 4-digit industries. This is one of the few studies of agglomeration effects on the location choices by foreign investments in transition economies in general and in Vietnam in particular. The estimates of the negative binomial regression model and the conditional logit model show that agglomeration benefits motivate foreign firms in the same industries and from the same countries of origin to locate near each other. However, the empirical results also indicate that there is competition among provinces in Vietnam in attracting foreign investors, and the locations of Vietnamese firms have no effects on the location decisions by foreign firms in the same industry.
Keywords: F23; 330; Agglomeration; Location choice; Foreign direct investment